Nurses and midwives' experiences of using non-pharmacological interventions for labour pain management: a qualitative study in Ghana - Edward Appiah Boateng; Linda Osaebea Kumi; Abigail Kusi-Amponsah Diji (BMC, 2019)
Abstract Background Non-pharmacological interventions hold promise in reducing labour pain, with minimal or no harm to the mother, foetus and the progress of labour and are simple and cost-effective. Yet their use has not been adequately explored in clinical settings, especially in sub-Saharan Africa. Methods This was a descriptive phenomenological study. Fifteen (15) nurses and midwives working in labour wards of two hospitals in Ghana were interviewed. Data analysis was guided by the principles of coding by Bailey and the constant comparative approach to generate themes. Ethics approval was obtained from the 37 Military Teaching Hospital Institutional Review Board in Ghana. Results Three major themes were identified that described the experiences of nurses and midwives regarding their use of non-pharmacological interventions in managing labour pain. These were familiarity with non-pharmacological interventions, perceived benefits of non-pharmacological interventions, and barriers to the use of non-pharmacological interventions in the management of labour pain. Conclusions While some non-pharmacological pain management interventions were known and used by the nurses and midwives, they were not familiar with a good number of these interventions. Nurses and midwives perceived these interventions to be beneficial yet a number of barriers prevented easy utilisation.